Impact of the January 2012 solar proton event on polar mesospheric clouds. Issue 15 (12th August 2016) - Bardeen, C. G.; Marsh, D. R.; Jackman, C. H.; Hervig, M. E.; Randall, C. E.
Abstract: We use data from the Aeronomy of Ice in the Mesosphere mission and simulations using the Whole Atmosphere Community Climate Model to determine the impact of the 23–30 January 2012 solar proton event (SPE) on polar mesospheric clouds (PMCs) and mesospheric water vapor. We see a small heating and loss of ice mass on 26 January that is consistent with prior results but is not statistically significant. We also find a previously unreported but statistically significant ~10% increase in ice mass and in water vapor in the sublimation area in the model that occurs in the 7 to 14 days following the start of the event. The magnitude of the response to the January 2012 SPE is small compared to other sources of variability like gravity waves and planetary waves; however, sensitivity tests suggest that with larger SPEs this delayed increase in ice mass will increase, while there is little change in the loss of ice mass early in the event. The PMC response to SPEs in models is dependent on the gravity wave parameterization, and temperature anomalies from SPEs may be useful in evaluating and tuning gravity wave parameterizations. Key Points: The 23‐30 January 2012 SPE caused an ~10% increase in PMCs mass seen by AIM and predicted by WACCM PMC increase is opposite in sign to the SPE effects previously reported Water vapor in the sublimation area may be a better indicator than ice mass of SPE effects on PMC